PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PERAWAT DI RUMAH SAKIT: KAJIAN LITERATUR - Dewi Agustina; Putri, Putri; Salsabila Lubis; Azrina Febriyani Nasution; Afifa Tohira; Sukma Hadisti Nasution; Nadiyah Azka Salsabilla Azizah; Annysha Maharani Harahap; Sapriya Zahara Larosa; Viola Safitri; Tria Annisa Ramadhani; Syahbrina Misella Damanik (Journal of Innovation Research and Knowledge, 2025)
Abstract: Nurses are health workers who play a vital role in providing health services in hospitals, both in technical and non-technical aspects. Good nurse performance is an important factor in improving service quality and patient safety. One factor that can affect nurse performance is the leadership style applied by superiors. This literature review aims to describe the influence of transformational leadership on nurse performance in hospitals. The research method was conducted through a literature review by examining various scientific articles from national and international journals that discuss the relationship between transformational leadership and nurse performance. The results of the study indicate that transformational leadership contributes positively to improved performance, job satisfaction, motivation, organizational commitment, and even the quality of patient care. The mechanism of influence of this leadership style lies in four main dimensions, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Through the application of these dimensions, leaders are able to foster self-confidence, stimulate creativity, and pay attention to the individual needs of staff, so that nurses feel valued and more motivated to provide optimal service. However, some studies have also found that the influence of transformational leadership on nurse performance is often mediated by other factors, such as organizational climate, psychological safety, and work culture. This indicates that transformational leadership is indeed important, but its effectiveness is highly dependent on the internal and external conditions of the hospital. Thus, the application of transformational leadership style is a relevant and potential strategy to improve nurse performance and the quality of health services in hospitals in a sustainable manner